Analysis of social problems of large families (based on a regional research) - Nadezhda Evgenievna Prodiblokh; Zaira Yunusovna Tuguz (Вестник Майкопского государственного технологического университета)
The research is aimed at identifying the problems of large families in the region, determining the role of the state in solving them, as well as studying the reasoned proposals of large families to expand and improve measures of state social support. The relevance of the topic is due not only to the important role of large families in the structure of its institution and society as a whole, but also to the fact that in the current socio-economic conditions it becomes almost impossible for the independent existence of this category without state support. In order to identify the optimal directions of the state social family policy, empirical sociological data have been obtained using the method of sociological survey of a sample of large families in the Republic of Adygea. The results have made it possible to identify the most effective measures of state support for large families, as well as, to improve social support programs, to identify contradictions and shortcomings of the current system that require further improvement. At the same time, solving the problem of social financing, highlighted by the respondents as a priority, cannot fully eliminate the remaining problems of large families, and insufficient attention to the issues of employment and education of the studied category will create the basis for the formation of a dependent behavior.